Industrial History of Instant Photography Polaroid 〜 Eastman Kodak 〜 Fuji Film - Mihayashi, Keiji (Journal of The Society of Photographic Science and Technology of Japan, 2025)
Instant photography, invented by Polaroid founder Dr. Land in 1947, was widely accepted by the world for its immediacy and convenience. The name “Polaroid” became synonymous with instant photography around the world, with Polaroid becoming one of the world's leading companies. Eastman Kodak, a giant in the photography industry, also entered the instant photography business, which was seen as promising, in 1972, but lost a patent dispute with Polaroid and Kodak withdrew from the instant photography business in 1986. Polaroid which won the dispute, was unable to provide products and services that were accepted by the market and its business declined in the 1980s, leading to the company going bankrupt. It is no longer in business. Meanwhile, Fuji Film avoided disputes with Polaroid and Kodak and formed a friendly relationship with them, entering the instant photography business in 1981, and has continued to expand and develop its business to this day, centering on the Instax.